When Does Old Become Too Old? - Woodward, Kathleen (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
“For Voters, When Does Old Become Too Old?”: this question heads the February 9, 2024 subscriber-only piece by Nate Cohn in The New York Times referring to the presumptive presidential contest in the U.S. between Joseph Biden and Donald Trump. The answer? “Polling shows it’s a broad concern expressed about President Biden, not just one person’s opinion.” Cohn’s piece, which prompted 1236 comments that very day (they constitute my dataset for this reflection), is only one in an avalanche in the news and on social media in the U.S. and beyond that provides us with a window into attitudes toward aging in general and aging in relation to the American presidency in particular.